Analisis Tingkat Layanan Ruas Jalan dan Persimpangan di Kecamatan Gandus Akibat Pembangunan Jalan Tol Kayu Agung – Palembang - Betung - Melawaty Agustien; Debby Yulinar (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2022)
The construction of Musi V Bridge is part of the series of Kapal Betung Toll Road, with the toll road in and out of Social Street which is connected to Lettu Karim Kadir Street. This study aims to obtain the performance of roads and intersections in Gandus District, obtain transportation modeling of traffic movements due to KayuAgung-Palembang-Betung Toll Road interchange, obtain predictions of the performance of roads and intersections resulting from traffic simulation models and provide policy suggestions in the form of strategies and traffic engineering management techniques. Data processing used the 2014 PKJI method and simulation with Vissim program. Results of data processing show that the performance of roads and intersections in existing conditions is still able to accommodate traffic flow, indicated by the degree of saturation that meets 2014 PKJI requirements, namely (DJ ≤ 0.85) with service level C and Vissim simulation results show the largest delay and queue length located in segment 3 (M Amin Fauzi Street -Tph Sofyian Kenawas Street) which is 138.18 meters and 21.02 seconds and on Lettu Karim Kadir Street (Direction of Musi II) of 14.04 seconds and 58.96 meters. After the operation of the Musi V Bridge, there was an increase in traffic volume which resulted in decreased performance of roads and intersections. Therefore, to improve its performance, road widening is carried out. The results of 2014 PKJI analysis showed a decrease in the degree of saturation from 0.43 to 0.35, a delay from 9.02 seconds / cur to 8.22 seconds / cur and the chances of queuing from 8.50 - 20.39% to 6.04 - 15.91% on Lettu Karim Kadir Street (Musi II Direction).